A co-design approach for the development and classroom integration of embodied learning apps - Georgiou, Yiannis; Ioannou, Andri (My University, 2020)
The development of embodied learning apps has gained traction in the recent years. However, current design approaches present two main limitations: (a) the inadequate involvement of teachers in the design process, and (b) the development of embodied apps, neglecting the context-specific requirements. It is, therefore, no surprising that teachers are often reluctant to integrate such innovations in their classrooms. In this paper we present a co-design approach to address these limitations, thus contributing to the smoother introduction of embodied apps in mainstream education. The suggested design approach was applied for the co-design of the “Young cardiologists” embodied app, including three sequential stages: Teachers as (a) “Users”, (b) “Content experts”, and (c) “Technology integrators”. The co-design approach ensured the active involvement of primary school teachers and guided the development of the app in alignment with the teachers’ educational curriculum. The evaluation of the co-designed app reported learning gains in children’s conceptual understanding.
Keywords: Curricula; Design; Human computer interaction; Co-design approach; Co-designs; Conceptual understanding; Design approaches; Design process; Learning gain; Primary schools; E-learning